Spatial distribution of lead and copper in the bottom sediments of Pahang River estuary, Pahang, Malaysia - Yunus, Kamaruzzaman; Ahmad, Siti Waznah; Ong, Meng Chuan; Bidai, Joseph (Penerbit UKM, 2010)
Bottom sediment samples from 30 stations of Pahang River estuary collected in April 2008 were analyzed for the concentration of Pb and Cu using the Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The average concentrations of Pb and Cu were 74.31 ± 22.97 μg/g dry weights and 18.65 ± 7.65 μg/g dry weights, respectively. In this study, the concentrations were significantly higher near the mouth river and declined as the sampling points were further away from the estuary. Generally, the concentrations of heavy metals were relatively low when compare with other studies in Malaysia. However, the calculated enrichment factors (EF) obtained for Pb, has a slightly higher value, and was probably influenced by anthropogenic input. The concentration for both metals increased with the decrease of mean size, suggesting their association with the fine fraction of the sediments.